The Development of the Polish National Cittaslow Network - Wierzbicka, Wioletta; Farelnik, Eliza; Stanowicka, Agnieszka (Olsztyn Economic Journal, 2019)
The purpose of this article has been to present the history of the Polish National Cittaslow Network, to discuss its development and to draw the attention to the diversity of network member cities. The authors emphasise the fact that the Polish National Cittaslow Network is developing very dynamically, and is the second largest network of Cittaslow in the world. Today, it is composed of 28 cities, of which 20 lie in the Warmińsko-Mazurskie Voivodeship. Other two centers are currently in the process of joining the network. The member cities are diverse in terms of their size as well as environmental or cultural assets. They are also diverse in terms of the level of socio-economic development. There are such cities in the network whose level of entrepreneurship, measured by the number of private sector businesses per 1,000 residents, is much higher than the average for the whole network (Rzgów, Murowana Goślina), but there are also cities with a very low level of entrepreneurship (Rejowiec Fabryczny, Jeziorany). Despite the differences, the cities associated in the network share the same concept and pursue shared aims in order to improve the quality of life for their inhabitants. They are proponents of implementing pro-social and pro-environmental measures, while striving to preserve the unique character of each of these cities.